Kajian Peranan Sektor Ekonomi Basis Terhadap Produk Domestik Regional Bruto (PDRB) Kabupaten Lamongan Tahun 2022 - Parikesit Penangsang; Pramita Studiviany; Adiati Trihastuti (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The improving condition of the regional economy can be seen through economic growth, of course this cannot be separated from the support of an increase in investment value. Lamongan Regency's long-term economic development aims to increase sustainable economic growth by providing investment opportunities for investors. A good investment climate is needed by investors so that their investments have a positive impact. Regional economic development hopes to have good progress and can increase the GRDP of Lamongan Regency. Various efforts have been made by the regional government to promote Lamongan Regency with the aim of attracting investor interest so that GRDP and Regional Income increase, as well as having a direct impact on equitable development in all fields. In this situation, there needs to be a phenomenal instrument to encourage the investment climate, by calculating 17 GRDP economic sectors, to find out which economic sectors have a basic economy, and this needs to be supported by the Lamongan Regency Regional Regulation. The GRDP of Lamongan Regency from 2017-2021 is a description of the economic activities of 17 GDP economic sectors which are experiencing fluctuations. Economic structure based on business field, rate of economic growth in a region, increase in prices of goods and services over one year, determination of base and non-base sectors, development of investment value based on target and realization, development of gross fixed capital formation, investment opportunities seen through the ICOR approach . The role of regional government as regional leaders and OPD as regional government organizers, needs to support economic activities so that GRDP in 2022 increases. Using the ICOR value can predict the amount of investment in the four sectors, namely the Agriculture, Forestry and Fisheries sectors amounting to IDR 7,115,508,510,000.00, the Processing Industry sector amounting to IDR 12,289,068,850,000.00, Wholesale and Retail Trade sector; Car and Motorbike repairs amounting to IDR 21,761,325,480,000.00, Real Estate sector amounting to IDR 2,809,442,040,000.00. This results in a prediction of the GRDP value increasing to Rp. 28,853,394,420,000 and investment/capital investment requirements to increase the GRDP of Lamongan Regency amounting to Rp. 15,580,832,990,000.00, this economic sector needs to be supported by a Regional Regulation concerning Providing Incentives and Facilitation of Regional Investment which has a positive impact on Investment and absorbs Lamongan Regency workforce.